Reimagining Studies’ Replication: A Validity-Driven Analysis of Threats in Empirical Software Engineering - Azevedo, Ivanildo; Vasconcelos, Ana Paula; Teixeira, Eudis; Soares, Sergio (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
Context: Replication studies play an important role in strengthening the empirical foundations of Software Engineering (SE). However, the existing literature reveals that the reporting of Threats to Validity (TTVs) remains inconsistent or superficial, potentially undermining the reliability of the replication results. Objective: The goal of this study is to analyze how replication studies consider TTVs present in original studies in SE. Method: We conducted a Systematic Literature Review (SLR) that resulted in 83 replication studies published between 2022 and 2024. We analyzed the presence and specificity of TTVs in four validity dimensions (construct, internal, external, and conclusion), considering different research methods and types of replication. Results: Our analysis shows that replication studies in Empirical Software Engineering (ESE) tend to report threats to validity more frequently and in greater detail than original studies, particularly with regard to external and internal validity. Nevertheless, threats related to the validity of the conclusion and construct remain underreported. We observed that controlled experiments generally address the different types of TTVs more comprehensively, whereas surveys and case studies provide more limited coverage. With respect to types of replication, close and differentiated replications are predominant, while conceptual and internal replications remain underexplored in the field. Conclusion: Although there is growing attention to the identification of TTVs in replication studies, reporting remains uneven across validity dimensions and study types. More structured and diverse replication strategies are needed, along with better guidelines to support comprehensive TTV reporting and enhance the rigor and methodological value of replication efforts in ESE.